Microheterogeneous singlet oxygen generation at air–water interfaces - Shaoping Mi; Ye-Guang Fang; Xiaochen Liu; Xiaoshan Zheng; Hongbo Ming; Xiaojiao Li; Baoliang Chen; Chongqin Zhu; Kristopher McNeill; Chiheng Chu (Proceedings of the National Academy of Sciences, 2026)
Singlet oxygen ( 1 O 2 ) is a short-lived, highly reactive oxidant driving natural element cycles, yet its spatial distribution in complex multiphase systems remains poorly understood. Here, we show that irradiation of organic carbon (OC)-containing aqueous microdroplets leads to pronounced interfacial enrichment of 1 O 2 , driven by the surface accumulation of photosensitizing OC. Combining fluorescence imaging with a reaction–diffusion kinetic model, we resolve steep 1 O 2 gradients across the air–water boundary: In a 1 µm-radius droplet, 1 O 2 levels drop by 90% within 10 µm from the interface into the gaseous phase, and within 230 nm from the interface into the aqueous phase. Tailored peptide probes reveal that molecules residing at the interface undergo substantially faster 1 O 2 -mediated transformation than their bulk counterparts. These findings identify the air–water interface as a privileged site for 1 O 2 photochemistry that strongly accelerates redox processes in aerosols, sea spray, and the ocean–atmosphere boundary.